2001
DOI: 10.2466/pr0.2001.88.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Humor and Empathic Concern

Abstract: A series of studies have shown that humor is associated with close interpersonal relationships and effective in reducing stress, which in turn enhances empathy. Therefore, it was hypothesized that humor and empathic concern would be positively correlated. The Empathic Concern subscale of the Empathy Questionnaire, the Coping Humor Scale, the Multidimensional Sense of Humor Scale, and the Situational Humor Response Questionnaire were given to 124 subjects. Scores on the Empathic Concern subscale were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…The indirect humour–health hypothesis, namely that humour or laughter may assist in moderating stress or enhance social competence and support, is more widely accepted (Nezlek & Derks 2001). Specific aspects such as empathy, intimacy and interpersonal trust (Hampes 1994, 1999, 2001) have all been positively correlated with sense of humour and subsequently with interpersonal relationships. Other researchers have attempted to correlate certain aspects of humour (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The indirect humour–health hypothesis, namely that humour or laughter may assist in moderating stress or enhance social competence and support, is more widely accepted (Nezlek & Derks 2001). Specific aspects such as empathy, intimacy and interpersonal trust (Hampes 1994, 1999, 2001) have all been positively correlated with sense of humour and subsequently with interpersonal relationships. Other researchers have attempted to correlate certain aspects of humour (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Some correlational studies have examined associations between trait measures of humor and several variables that are relevant to intimate relationships. For example, prior research has demonstrated that various self‐report sense of humor scales are positively correlated with measures of intimacy (Hampes, 1992), empathy (Hampes, 2001), social assertiveness (Bell, McGhee, & Duffey, 1986), and interpersonal trust (Hampes, 1999). Studies of dating and married couples have also shown that the more individuals perceive their partner to have a good sense of humor, the more they tend to be satisfied with the relationship (Rust & Goldstein, 1989; Ziv & Gadish, 1989).…”
mentioning
confidence: 99%
“…Humorous interactions can be thought of as a microcosm of secure attachment dynamics, but as yet little attention has been paid to humor in infancy or its association with emerging processes like attachment, despite their concurrent development in the first year of life. Research examining adult relationships shows humor is related to a variety of attachment-like variables (Hampes, 1992, 1999, 2001), beckoning attention to the humor-attachment association in parent-infant relationships.…”
Section: 3 Discussionmentioning
confidence: 99%
“…Humorous exchanges between infants and parents may enhance their opportunities to develop a satisfying relationship, an idea that is consistent with research on humor and relationship quality in adulthood. For example, among adults, humor has been associated with greater capacity for intimacy and the ability to establish deep affective relationships (Hampes, 1992) as well as empathic concern (Hampes, 2001) and trust (Hampes, 1999), the latter of which is considered necessary for attachment. Cann, Norman, Welbourne, and Calhoun (2008) reported that the four main humor styles measured in adults closely parallel empirically-supported attachment dimensions.…”
mentioning
confidence: 99%